ELAZIĞ İLİ KENTSEL ATIKSULARINDA ORGANİK KİRLİLİK YÜKÜNÜN BELİRLENMESİ - AYDIN, YUNUS (Fırat Üniveristesi, 2009)
Bu çalışmada, Elazığ Kenti ve Elazığ Kenti kanalizasyon sistemine bağlı olan beldelerin evsel atık sularında organik maddelerden, koliform ve E.coli'den kaynaklanan kirliliğin miktarı mevsimsel (ekim, ocak, nisan, temmuz ayları) olarak incelenmiştir. Araştırma kapsamında atık suyun debi, sıcaklık, çözünmüş oksijen (ÇO), biyokimyasal oksijen ihtiyacı (BOİ), kimyasal oksijen ihtiyacı (KOİ), amonyum azotu, yağ ve gres, askıda katı madde, total koliform, fekal koliform ve Escherichia coli parametreleri incelenmiştir. Araştırma neticesinde debi 40.711-52.170 m³/gün, BOİ 60,4-540 mg/L, KOİ 242,4-812 mg/L, AKM 65-388 mg/L, amonyum azotu 0,93-2,1 mg/L, yağ ve gres 32-54,4 mg/L aralıklarında, fekal koliform, total koliform ve Escherichia coli değerleri hepsi için 1100 EMS/mL `den daha büyük miktarlarda tespit edilmiştir.Yapılan hesaplamalar doğrultusunda arıtılmadan sucul ortama verilecek atık suyun günlük ortalama meydana getireceği yükler 12.343 kg/gün BOİ , 27.135 kg/gün KOİ, 11.541 kg/gün AKM, 71 kg/gün amonyum azotu ve 2.031 kg/gün yağ ve gres olarak hesaplanmıştır. Yıllık ortalama meydana getirecekleri yükler ise 4.505 ton/yıl BOİ, 9.904 ton/yıl KOİ, 4.212 ton/yıl AKM, 25 ton/yıl amonyum azotu, 741 ton/yıl yağ ve gres olarak hesaplanmıştır.Anahtar Kelimeler: Organik kirlilik, BOİ, KOİ, AKM, Amonyum azotu, Yağ ve gres, Fekal Koliform, Total Koliform, E.coli, Evsel atıksu, Elazığ

In this study, the level of pollution in the domestic sewage water of Elazığ City originated from organic matters, coliform bacteria and Escherichia coli has been investigated monthly (October, January, April, July). In the coverage of the study values belonging to the parameters of the flow rate, water temperature, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammonium nitrogen, oil and grease, suspended solid matters, total coliform, fecal coliform and Escherichia coli in the sewage water have been measured and/or analysed. The values for the above mentioned parameters have been determined within the following ranges; the flow rate 40.711-52.170 m3/day, BOD 60,4-540 mg/L, COD 242,4-812 mg/L, suspended solid matters 65-388 mg/L, ammonium nitrogen 0,93-2,1 mg/L, oil and grease 32-54,4 mg/L . The values for all fecal coliform, total coliform and E. coli have been determined in quantities more than 1100 EMS/mL.In accordance with the calculations performed, the daily average loads of the raw sewage water were found as follows; 12,343 kg/day for BOD, 27,135 kg/day for COD, 11,541 kg/day for suspended solid matters, 71 kg/day for ammonium nitrogen and 2,031 kg/day for oil and grease. The annual loads have been calculated as 4,505 tons/year for BON, 9,904 tons/year for CON, 4,212 tons/year for suspended solid matters, 25 tons/year for ammonium nitrogen and 741 tons/year for oil and grease.Keywords: Organic Pollution, BON, CON, Suspended Solid Matters, Ammonium Nitrogen, Oil and Grease, Fecal Coliform, Total Coliform, Escherichia coli, Domestic Sewage Water, Elazığ.
The organic pollution load of the urban sewage water of Elaziğ city
Keywords: Su Ürünleri